Diversidade funcional em uma comunidade de floresta úmida: Testando fatores abióticos locais como filtros ambientais. - Gomes, José Leonardo dos Santos (2019)
Abiotic factors can act as environmental filters at the local level and influence the establishment, distribution and functional diversity in plant communities in a rainforest, with this premise the present study was carried out at Mata do Pau Ferro State Park, Paraíba, Northeast, Brazil. The functional diversity was calculated using an index based on dendrograms and from eight functional attributes: Specific Foliar Area (SLA), Foliar Blade Size (SL), Basic Wood Density (BWD), Maximum Height (H), Material Content Dry Foliar (LDMC). Basal area (BA), Limbo Division (LBD) and Deciduity (DEC). (FD) as a dependent variable of the following predictive variables: soil fertility represented in this study by the organic matter content and the saturation value of the bases, soil chemistry represented by the components PH, amount of phosphorus (P) , potassium (K), sodium (Na), Aluminum (Al), Calcium (Ca), Magnesium (Mg), Potential Acidity (H ++ Al + 3) sum of bases (SB), cation exchange capacity soil physics represented by the descriptors total porosity and density, canopy opening, altitude, slope and distance of disturbed landscape. Through multiple linear regression analyzes Stepwise we selected the best model using the AIC criterion. 870 individuals belonging to 31 species distributed in 18 families and from their vegetative attributes, functional diversity was calculated, varying significantly as a function of altitude (p <0.001), organic matter and potassium content (p = 0.012926) and soil physics (p <0.001). Thus, local variations in altitude and soil acted as filters, so that, in the studied community, functional diversity reduces in areas with higher concentration of organic matter and increases in areas of higher altitude, more dense and porous soils.